RANCANG BANGUN APLIKASI PROGRAM SCHOOL PARENTING TERHADAP PEMBINAAN MORAL SISWA PADA SEKOLAH MENENGAH PERTAMA NEGERI 43 PADANG - Rakhel Cakra Sandika; Muhammad Adri; Dony Novaliendry; Yeka Hendriyani (Jurnal Humaniora & Sosial Sains, 2025)
Based on perceptions at SMP Negeri 43 Padang, it can be seen that there are a few issues that happen in child rearing exercises counting, need of data around children to guardians and instructors, visit delays in data approximately children from guardians to instructors, trouble finding arrangements to children's issues, and need of space to supply security data. The strategy utilized in planning this framework is the waterfall method. The waterfall method includes a handle that's simple to get it and the forms don't cover. In this strategy, one prepare must be completed in arrange to be able to continue to the following handle. Child rearing exercises at SMP Negeri 43 Padang point to empower guardians to move forward information, demeanors and abilities in shaping parenting patterns inside the family, as for the point of child rearing instruction at SMP Negeri 43 Padang, to be specific to extend social passionate ties between guardians, teachers and children. The application that has been built can make it simpler for the school and guardians of SMP N 43 Padang to create children's ethics. This application makes it simple for all parties to get it children's ethical improvement and give suitable exhortation to assist all parties.